2014
DOI: 10.1016/j.aoas.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and irrigation requirements of faba-bean in North Delta of Egypt in relation to planting dates

Abstract: Two field experiments were carried out in El-Bosaily farm in the Northern coast of Egypt

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 9 publications
10
16
0
1
Order By: Relevance
“…The yield of the plants observed on this study agrees with Hegab et al (2014). Those authors observed high productivity index in plants with low water available.…”
Section: Inovagri International Meeting 2017supporting
confidence: 82%
“…The yield of the plants observed on this study agrees with Hegab et al (2014). Those authors observed high productivity index in plants with low water available.…”
Section: Inovagri International Meeting 2017supporting
confidence: 82%
“…These results could be attributed to the higher grain yield under I 2 treatment comparable to I 1 and I 3 treatments. Similar results were obtained by Hegab et al (2014) and Ewis et al (2015).…”
Section: Water Utilization Efficiency (Wute Kg M-3)supporting
confidence: 89%
“…Although yield is still a crucial factor, studying how sowing date affects chemical and nutritional composition of seeds, may be helpful in achieving the desired quality of the product. Sowing date and densities have already been reported to influence the chemical composition of different legume crops such as chickling vetch (De Falco and Pardo, 1999;Rao and Northup, 2008), bean (Greven et al, 2004;Getachew et al, 2015), green field pea (Gubbels, 1977), faba bean (Hegab et al, 2014), soybean (Li, 2014) but, according to our knowledge, no data are available for chickpea. Hence, the aim of this study was to verify the hypothesis that different seeding practices (time and rate) can affect not only grain yield, but also nutritional composition, total tannins content and the susceptibility to Ascochyta blight of two chickpea cultivars (Sultano and Pascià) currently cultivated in the Mediterranean basin.…”
Section: Introductionmentioning
confidence: 98%